An Innovative Photogrammetric System for 3D Digitization of Dental Models - Zeljko Santosi; Igor Budak; Mario Sokac; Milos Kuzmanovic; Djordje Vukelic (Tehnički Vjesnik, 2022)
This paper presents an innovative system for 3D reconstruction of a physical dental model. The innovative system is based on close-range photogrammetry and enables the projection of digital light texture on the objects surface. It is based on the application of mirrors that direct the digital light texture to the vertical surfaces of the physical model. In this way, high coverage of the object is achieved, and 3D reconstruction from one set of photographs is possible. 3D digitization, verification and comparison of the proposed methodology was performed on dental models that are characterized by extremely complex surfaces. It was performed by comparing the proposed approach with active stereovision, and the efficiency was evaluated in relation to the reference 3D model obtained by the structured light 3D scanner. The comparison of the results was performed on the basis of the mean deviation and standard deviation for the 3D model with combined teeth and for the 3D model with metal caps. The absolute mean deviations for the 3D model with combined teeth are 0.004-0.021 mm, with a standard deviation of 0.055-0.058 mm, and for the 3D model with metal caps absolute mean deviations are 0.015-0.033 mm, with a standard deviation of 0.095-0.113 mm, respectively. Absolute minimum values of mean deviation of 0.004 mm and standard deviations of 0.055 mm were obtained by 3D model with combined teeth,which was reconstructed by the proposed innovative approach. The obtained results indicate a higher accuracy of the innovative approach in relation to the use of a commercial 3D scanner that uses active stereovision principle.